Estimating the population health and economic impacts of introducing a pneumococcal conjugate vaccine in Malaysia- an economic evaluation. Issue 7 (2nd July 2020) - Shafie, Asrul Akmal; Ahmad, Norazah; Naidoo, Jerusha; Foo, Chee Yoong; Wong, Callix; Pugh, Sarah; Tan, Kah Kee
ABSTRACT: Pneumococcal disease is a potentially fatal bacterial infection that is vaccine-preventable. Malaysia has yet to adopt a pneumococcal conjugate vaccine (PCV) into its national immunization program (NIP). In 2016, pneumonia was the 3 rd leading cause of death in children under five in Malaysia, accounting for 3.8% of under-five deaths. Introducing a pneumococcal conjugate vaccine (PCV) is an effective strategy to reduce the disease burden. This study used a decision-analytic model to assess the potential impacts of introducing the available PCVs (13-valent and 10-valent) in Malaysia. Epidemiological and costs inputs were sourced from published literature. For each vaccination program, health outcomes and associated healthcare costs were estimated. The scenarios of initiating PCV13 vs . PCV10 and the status quo (no pneumococcal vaccine) were compared. Serotype trends of Finland and the U.K. were used to model the clinical impacts of PCV10 and PCV13 respectively. The base-case analysis used a societal perspective over a 5-year time horizon. Compared with PCV10, PCV13 was projected to avert an additional 190, 628 cases of pneumococcal disease and 1126 cases of death. The acquisition of PCV13 was estimated to cost an incremental US$89, 904, 777, offset by a cost reduction of -US$250, 219, 914 on pneumococcal disease-related medical care and lost productivity. PCV13 demonstrated a higher cost-saving potential over PCV10. Compared with no vaccination, PCV13 was estimated as cost-saving. Results were robust across a series of sensitivity analyses. The introduction of PCV13 in a NIP was estimated to reduce a significant burden of disease and to be a cost-saving for the Malaysian health system.